Education and Development in the Sino‑African Context of Relations - István Tarrósy; Zoltán Vörös (Politeja, 2016)
This study focuses on the involvement of China in the above two African states, arguing that the development of the education sector, therefore the development via education is crucial for any of the states of the continent. It gives an overview of education as a significant aspect of human development in the context of opposing policies of the international financial institutions (IFIs) and the Chinese government. In the light of the FOCAC process, China’s involvement in the development of human resources on African soil will be looked at closely, also questioning whether or not China may present an ‘alternative’ to the IFIs in the field.